Formate-driven catalysis and mechanism of an iridium–copper complex for selective aerobic oxidation of aromatic olefins in water. Issue 16 (22nd March 2021) - Shimoyama, Yoshihiro; Kitagawa, Yasutaka; Ohgomori, Yuji; Kon, Yoshihiro; Hong, Dachao
Abstract : A hetero-dinuclear Ir III –Cu II complex with two adjacent sites was employed as a catalyst for the aerobic oxidation of aromatic olefins driven by formate and promoted by a hydrophobic interaction in water. Abstract : A hetero-dinuclear Ir III –Cu II complex with two adjacent sites was employed as a catalyst for the aerobic oxidation of aromatic olefins driven by formate in water. An Ir III –H intermediate, generated through formate dehydrogenation, was revealed to activate terminal aromatic olefins to afford an Ir-alkyl species, and the process was promoted by a hydrophobic [Ir III –H]-[substrate aromatic ring] interaction in water. The Ir-alkyl species subsequently reacted with dioxygen to yield corresponding methyl ketones and was promoted by the presence of the Cu II moiety under acidic conditions. The Ir III –Cu II complex exhibited cooperative catalysis in the selective aerobic oxidation of olefins to corresponding methyl ketones, as evidenced by no reactivities observed from the corresponding mononuclear Ir III and Cu II complexes, as the individual components of the Ir III –Cu II complex. The reaction mechanism afforded by the Ir III –Cu II complex in the aerobic oxidation was disclosed by a combination of spectroscopic detection of reaction intermediates, kinetic analysis, and theoretical calculations.